Flexible pressure sensor based on cellulose solid electrolyte membrane

By using phosphoric acid and urea phosphate dissolving systems to prepare a cellulose solid electrolyte membrane and combined with PI gold depositing electrodes, the existing pressure sensors have been solved, such as slow response time, poor stability, poor oxidation resistance and high preparation cost, and the pressure sensing effect of fast response, high stability, strong oxidation resistance and environmentally friendly and low-cost.

CN119779521AActive Publication Date: 2025-04-08EAST CHINA NORMAL UNIV

Patent Information

Application Number
CN202411983079.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

Existing pressure sensors have problems such as slow response time, poor stability, poor oxidation resistance and high preparation cost, and it is difficult to meet the needs of fast response, high stability, strong oxidation resistance and low environmental protection.

Method used

A cellulose solid electrolyte membrane is prepared by a dissolving system of phosphoric acid and urea phosphate, and combined with a PI gold depositing electrode to achieve pressure sensing through the principle of electric double layer capacitance.

Benefits of technology

It achieves rapid response, high stability, strong oxidation resistance and environmentally friendly and low-cost pressure sensing effect, improving the reliability and life of the sensor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119779521A_ABST
    Figure CN119779521A_ABST
Patent Text Reader

Abstract

The invention relates to a flexible pressure sensor based on a cellulose solid electrolyte membrane, and belongs to the field of medical health. A cellulose solid electrolyte membrane of a phosphoric acid and urea phosphate dissolution system and a PI gold immersion electrode are adopted; the phosphoric acid and the urea phosphate can be used as a dissolving system of the cellulose and an electrolyte system of the electrolyte membrane, so that the preparation steps of the electrolyte membrane are simplified, and meanwhile, the electrolyte membrane has good chemical stability and oxygen resistance. Phosphoric acid and urea phosphate are completely degradable components and are more environment-friendly than a conventional electrolyte system. The gold layer, the nickel layer and the PI film of the PI gold immersion electrode can form an embedded interlocking structure, so that the combination is tighter, the stability and the mechanical property are enhanced, and meanwhile, the excellent conductive performance can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a flexible pressure sensor based on a cellulose solid electrolyte membrane, belonging to the field of medical health. Background Art

[0002] At present, pressure sensors are mainly divided into three categories: electrochemical pressure sensors based on metal corrosion effect, flexible pressure sensors based on ion paper, and pressure sensors based on MXene materials.

[0003] Electrochemical pressure sensor based on metal corrosion effect: The working principle is that the migration of ions in the solid electrolyte under pressure accelerates the corrosion reaction of different electrodes (such as zinc and carbon electrodes), resulting in a change in potential difference, and the pressure is reflected by detecting the potential difference. It includes a solid electrolyte layer and two metal electrodes with different corrosion activities. The pressure causes the contact area between the electrolyte and the electrode to change, thereby changing the electrochemical reaction rate. Its main disadvantages are slow response time. Since the corrosion reaction takes a certain amount of time, the dynamic response speed of the sensor is limited; the reliability is poor after long-term use, and the irreversibility of metal corrosion may cause the sensor performance to decline and the life to be short.

[0004] Flexible pressure sensor based on ion paper: The pressure is measured by changing the contact area between the folded ion paper and the electrode, causing the change of the double-layer capacitance. The sandwich structure of the electrode / ion paper / electrode is face-to-face contact; the electrode screen-prints the conductive silver paste on the designed area of ​​the ion paper surface to form a specific electrode pattern; the ion paper is folded to form a sensitive area. Limited mechanical strength: The mechanical strength of the ion paper is low and it is easily damaged under high pressure conditions; there are stability problems, the stability of the ion material is poor, and it may decompose or produce side reactions in high temperature, high potential or strong oxidizing environment; there is a risk of environmental pollution, and the side reactions or decomposition of the ion material will produce toxic byproducts, which pose a threat to the environment; the preparation cost is high, the liquid ion material and its composite preparation process with the matrix are relatively complicated, and the electrode is prepared by screen printing conductive silver paste, which has poor stability.

[0005] Pressure sensor based on MXene materials: Utilizing the high conductivity and variable resistance characteristics of MXene materials, when pressure acts on the sensor, the microstructure within the material changes, causing the resistance to change, thereby detecting pressure. The structure includes a MXene conductive layer, a flexible substrate (such as PDMS or TPU), and a protective layer. The MXene layer is prepared by coating or printing technology to form a pressure-sensitive film. MXene materials are easily oxidized in the air, resulting in degradation of electrical properties and affecting the long-term stability of the sensor; the preparation of MXene involves a complex chemical etching process, and the preparation cost is high, which limits large-scale commercial applications. Summary of the invention

[0006] According to the background problem, the problem to be solved by the present invention is:

[0007] How to prepare a pressure sensor with fast response, high stability, oxidation resistance, environmental protection and low cost.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] A flexible pressure sensor based on cellulose solid electrolyte membrane, using a cellulose solid electrolyte membrane in a phosphoric acid and urea phosphate dissolution system and a PI immersion gold electrode;

[0010] The preparation steps of the cellulose solid electrolyte membrane are:

[0011] S1. adding urea phosphate and cellulose to phosphoric acid, and completely mixing and dissolving them by ultrasonication to obtain a mixed solution 1;

[0012] S2. PVA is added to deionized water, heated to melt at 90 to 95°C, and the PVA and water are mixed uniformly by stirring to obtain a PVA solution;

[0013] S3. Add the mixed solution 1 obtained in step S1 dropwise to the PVA solution obtained in step S2, and keep stirring during the addition process; obtain an electrolyte solution in which cellulose is dissolved, i.e., a mixed solution 2; the mass ratio of the mixed solution 1 added dropwise to the PVA solution is 1:10 to 1.3:10;

[0014] S4. Pour the mixed solution 2 obtained in step S3 into a mold and dry it in a constant temperature drying oven at 30 to 35°C for 24 to 48 hours to obtain a cellulose solid electrolyte membrane;

[0015] The steps for preparing the PI immersion gold electrode are as follows:

[0016] (1) cleaning the PI film by ultrasonic wave, placing the cleaned PI film in KOH solution for modification, and obtaining a modified PI film;

[0017] (2) immersing the modified PI film in a nickel sulfate solution at 45 to 50° C., so that nickel ions are adsorbed on the surface of the PI film, thereby obtaining a PI film adsorbed with nickel ions;

[0018] (3) placing the PI film adsorbed with nickel ions in a sodium borohydride solution to reduce a nickel seed layer on the surface of the PI film to obtain a reduced PI film;

[0019] (4) placing the reduced PI film into a nickel precipitation solution at 85-90° C., a dense nickel layer will grow on the surface of the PI film, and a nickel-treated PI film will be obtained;

[0020] (5) The nickel-treated PI film is immersed in a gold-immersion solution at 85 to 90°C. At this time, a uniform and dense gold layer will grow on the surface of the PI film to obtain a PI gold-immersion electrode.

[0021] Preferably, the cellulose solid electrolyte membrane has micro-columnar protrusions on its surface after being dried in a mold.

[0022] Preferably, in step S1, the concentration of phosphoric acid is 85 wt %, and the mass ratio of urea phosphate, cellulose and phosphoric acid solution is 1:2 to 6:1.74.

[0023] Preferably, in step S3, the mass ratio of the amount of the mixed solution 1 added to the PVA solution is 1:10.

[0024] Preferably, the concentration of the KOH solution in step (1) is 4 M, the concentration of the nickel sulfate solution in step (2) is 0.05 M, the concentration of the sodium borohydride solution in step (3) is 0.025 M, and the nickel precipitation solution and gold precipitation solution are produced by Shenzhen Kosilin Surface Treatment Materials Co., Ltd., and the nickel precipitation solution model is KS-N110, and the gold precipitation solution model is HAU-99.

[0025] The electrolyte membrane uses the principle of double-layer capacitance. The principle of double-layer capacitance is that when the two electrodes of the capacitor are immersed in the electrolyte and voltage is applied, the surface of the conductive electrode will adsorb ions with opposite charges (such as positive charges adsorbing negative ions), and the ions in the electrolyte are close to the electrode surface to form an ion-enriched layer. This double layer composed of the charge on the electrode and the ions in the electrolyte is called a double layer. The double layer is transformed into a double-layer capacitor. Its working mechanism is that the electrode surface adsorbs ions with opposite charges to form a double layer. Energy is stored at the interface between the electrode and the electrolyte. No chemical reaction is involved. During the charge and discharge process, the ions only move in the electrolyte and do not participate in the reaction of the electrode material.

[0026] What is used in the present invention is the phosphoric acid / urea phosphate system to dissolve cellulose. Compared with the conventional ionic material dissolving cellulose, phosphoric acid is a common chemical with abundant raw materials and mature preparation technology. Urea phosphate is commonly used in fertilizers, soil conditioners and water treatment fields. This method has lower cost and does not require a complicated preparation method. Phosphoric acid and urea phosphate are both completely degradable ingredients, which are more environmentally friendly. Phosphoric acid has stable chemical properties and strong oxidation resistance. The present invention also uses it as an electrolyte system, and the solid cellulose electrolyte membrane has good chemical stability and oxygen resistance. The electrolyte membrane with added cellulose has high mechanical strength, can withstand greater forces, and is not easily damaged.

[0027] The solid electrolyte membrane with added cellulose material is prepared into a micro-column through a mold. Under the action of pressure, the electrolyte membrane will deform, resulting in a change in the contact area between the electrolyte membrane and the electrode. A double-layer capacitor will be formed in the contact part between the electrolyte membrane and the electrode. The change in capacitance can reflect the change in force. The advantage is that the charging and discharging speed is fast, so the response speed is fast, the ions only move in the electrolyte, there is no chemical reaction, and the long-term reliability is good.

[0028] The present invention adopts a PI thin film gold-immersion electrode. The principle is that potassium carboxylate will be produced on the surface of the PI thin film under the modification effect of the strong alkaline solution KOH. When the PI thin film modified by KOH is immersed in a NiSO4 solution, ion exchange will occur between K+ and Ni2-. After the ion exchange, the nickel ions will be embedded in the surface structure of the PI thin film. Then, the reducing property of NaBH4 can be used to reduce Ni2+ to a Ni seed layer. On the basis of the seed layer, the PI surface is treated with a nickel-immersion solution to obtain a uniform and dense Ni metal layer. Subsequently, limited redox substitution occurs on the PI surface through the gold-immersion solution to obtain AuNPS deposited on the Ni-P layer. As the reaction time increases, a dense and stable Au layer is formed.

[0029] The gold layer, nickel layer and PI film will form an embedded interlocking structure, which is more tightly combined, enhancing stability and mechanical properties, and can achieve excellent conductive properties. The thickness of the PI immersion gold electrode depends on the thickness of PI, which can reach 25 microns, which is thinner and lighter, and retains the excellent flexibility of the PI film.

[0030] The beneficial effects of the present invention are:

[0031] 1. Phosphoric acid and urea phosphate can be used as both a dissolving system for cellulose and an electrolyte system for the electrolyte membrane, which simplifies the preparation steps of the electrolyte membrane and at the same time makes the electrolyte membrane have good chemical stability and oxygen resistance.

[0032] 2. Phosphoric acid and urea phosphate are both completely degradable ingredients and are more environmentally friendly than conventional electrolyte systems.

[0033] 3. The gold layer, nickel layer and PI film of the PI immersion gold electrode will form an embedded interlocking structure, which is more tightly combined, enhancing the stability and mechanical properties while achieving excellent conductive properties.

[0034] 4. The flexible pressure sensor obtained by the present invention adopts a cellulose solid electrolyte membrane and a PI immersion gold electrode, which makes the flexible pressure sensor respond faster, have higher stability, be more resistant to oxidation, and have low environmental protection cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1Pressure-capacitance relationship diagram of the flexible pressure sensor made of the cellulose solid electrolyte membrane sample of Example 1

[0036] Figure 2 Response and recovery time diagram of the flexible pressure sensor made of the cellulose solid electrolyte membrane sample of Example 1

[0037] Figure 3 Pressure-capacitance relationship diagram of the flexible pressure sensor made of the cellulose solid electrolyte membrane sample of Example 2

[0038] Figure 4 Response and recovery time diagram of the flexible pressure sensor made of the cellulose solid electrolyte membrane sample of Example 2

[0039] Figure 5 Pressure-capacitance relationship diagram of the flexible pressure sensor made of the cellulose solid electrolyte membrane sample of Example 3

[0040] Figure 6 Response and recovery time diagram of the flexible pressure sensor made of the cellulose solid electrolyte membrane sample of Example 3 DETAILED DESCRIPTION

[0041] In the following embodiments, the basic structure of the flexible sensor is that the top and bottom layers are PI immersion gold electrodes with a thickness of 25um, the middle interlayer is a silicone support layer with a thickness of 150um, the silicone support layer has a hole in the center, and a cellulose solid electrolyte membrane is placed in the hole. The cellulose solid electrolyte membrane is divided into two parts, the bottom layer is a large disc with a diameter of 6mm and a height of 50um, and the upper layer is 4 micro cylinders with a diameter of 1mm and a height of 100um, providing sensitive deformation. The electrolyte membrane can be prepared into any shape using other molds as needed, all of which belong to the protection scope of this patent.

[0042] The nickel immersion solution and gold immersion solution used are both from Shenzhen Kesilin Surface Treatment Materials Co., Ltd. The nickel immersion solution model is KS-N110, and the gold immersion solution model is HAU-99.

[0043] Example 1

[0044] Preparation of cellulose solid electrolyte membrane:

[0045] S1. 0.1 g of urea phosphate and 0.6 g of cellulose were added to 5 ml of phosphoric acid and stirred for 15 minutes by ultrasonic dispersion to completely mix and dissolve the mixture to obtain a mixed solution 1;

[0046] S2. 2 g of PVA was added to 18 ml of deionized water and heated to melt at 95 ° C; a magnetic stirrer was used to stir at 1000 rpm for 5 minutes to mix the PVA and water evenly to obtain a PVA solution;

[0047] S3. The mixed solution 1 obtained in step S1 is added dropwise to the PVA solution obtained in step S2 in an amount of 2.17 g, and stirring is maintained during the addition process; an electrolyte solution containing cellulose is obtained, namely, a mixed solution 2;

[0048] S4. Pour the mixed solution 2 obtained in step S3 into a mold, and dry it in a constant temperature drying oven at 30° C. for 24 hours to obtain a cellulose solid electrolyte membrane.

[0049] Preparation of PI immersion gold electrode:

[0050] (1) Cleaning the PI film by ultrasonic wave, placing the cleaned PI film in a 4M KOH solution for modification, and obtaining a modified PI film;

[0051] (2) immersing the modified PI film in a 0.05 M nickel sulfate solution at 50° C., so that nickel ions are adsorbed on the surface of the PI film, thereby obtaining a PI film adsorbed with nickel ions;

[0052] (3) placing the PI film adsorbed with nickel ions in a 0.025 M sodium borohydride solution to reduce a nickel seed layer on the surface of the PI film to obtain a reduced PI film;

[0053] (4) placing the reduced PI film into a nickel precipitation solution at 95°C, a dense nickel layer will grow on the surface of the PI film, and a nickel-treated PI film will be obtained;

[0054] (5) The nickel-treated PI film is immersed in a 95°C gold-immersion solution. At this time, a uniform and dense gold layer will grow on the surface of the PI film to obtain a PI gold-immersion electrode.

[0055] Depend on Figure 1 As can be seen from the figure, the curve is the relationship between pressure and capacitance. The sensitivity is 0.49 in 0-2N, 0.38 in 2-4N, and 0.24 in 4-10N. The linearity of the corresponding range is 1%, 1.1%, and 0.9%. In the range of 0-10N, the sensitivity is 0.3 and the linearity is 2.46%.

[0056] Depend on Figure 2 It can be seen from the response time curve that the response time and recovery time of the sensor are both 380ms.

[0057] Example 2

[0058] Preparation of cellulose solid electrolyte membrane:

[0059] S1. 0.1 g of urea phosphate and 0.4 g of cellulose were added to 5 ml of phosphoric acid and stirred for 15 minutes by ultrasonic dispersion to completely mix and dissolve the mixture to obtain a mixed solution 1;

[0060] S2. 2 g of PVA was added to 18 ml of deionized water and heated to melt at 90 ° C; a magnetic stirrer was used to stir at 1000 rpm for 5 minutes to mix the PVA and water to obtain a PVA solution;

[0061] S3. The mixed solution 1 obtained in step S1 is added dropwise to the PVA solution obtained in step S2 in an amount of 2.6 g, and stirring is maintained during the addition process; an electrolyte solution containing cellulose is obtained, namely, a mixed solution 2;

[0062] S4. Pour the mixed solution 2 obtained in step S3 into a mold, and dry it in a constant temperature drying oven at 35° C. for 36 hours to obtain a cellulose solid electrolyte membrane.

[0063] Preparation of PI immersion gold electrode:

[0064] (1) Cleaning the PI film by ultrasonic wave, placing the cleaned PI film in a 4M KOH solution for modification, and obtaining a modified PI film;

[0065] (2) immersing the modified PI film in a 0.05 M nickel sulfate solution at 50° C., so that nickel ions are adsorbed on the surface of the PI film, thereby obtaining a PI film adsorbed with nickel ions;

[0066] (3) placing the PI film adsorbed with nickel ions in a 0.025 M sodium borohydride solution to reduce a nickel seed layer on the surface of the PI film to obtain a reduced PI film;

[0067] (4) placing the reduced PI film into a nickel precipitation solution at 90°C, a dense nickel layer will grow on the surface of the PI film, and a nickel-treated PI film will be obtained;

[0068] (5) The nickel-treated PI film is immersed in a 90°C gold-immersion solution. At this time, a uniform and dense gold layer will grow on the surface of the PI film to obtain a PI gold-immersion electrode.

[0069] Depend on Figure 3 It can be seen that the sensitivity of the curve is 0.28 in the range of 0-2N, 0.38 in the range of 2-4N, and 0.17 in the range of 4-10N. The linearity is 2.7% in the range of 0-2N, 3.2% in the range of 2-4N, and 1.1% in the range of 4-10N.

[0070] Depend on Figure 4It can be seen from the response time curve that the response time and recovery time of the sensor are both 370ms.

[0071] Example 3 Preparation of cellulose solid electrolyte membrane:

[0072] S1. 0.1 g of urea phosphate and 0.2 g of cellulose were added to 5 ml of phosphoric acid and stirred for 15 minutes by ultrasonic dispersion to completely mix and dissolve the mixture to obtain a mixed solution 1;

[0073] S2. 2 g of PVA was added to 18 ml of deionized water and heated to melt at 90 ° C; a magnetic stirrer was used to stir at 1000 rpm for 5 minutes to mix the PVA and water to obtain a PVA solution;

[0074] S3. The mixed solution 1 obtained in step S1 is added dropwise to the PVA solution obtained in step S2 in an amount of 2.0 g, and stirring is maintained during the addition process; an electrolyte solution containing cellulose is obtained, namely, a mixed solution 2;

[0075] S4. Pour the mixed solution 2 obtained in step S3 into a mold, and dry it in a constant temperature drying oven at 35° C. for 48 hours to obtain a cellulose solid electrolyte membrane.

[0076] Preparation of PI immersion gold electrode:

[0077] (1) Cleaning the PI film by ultrasonic wave, placing the cleaned PI film in a 4M KOH solution for modification, and obtaining a modified PI film;

[0078] (2) immersing the modified PI film in a 0.05 M nickel sulfate solution at 45° C., so that nickel ions are adsorbed on the surface of the PI film, thereby obtaining a PI film adsorbed with nickel ions;

[0079] (3) placing the PI film adsorbed with nickel ions in a 0.025 M sodium borohydride solution to reduce a nickel seed layer on the surface of the PI film to obtain a reduced PI film;

[0080] (4) placing the reduced PI film into a nickel precipitation solution at 90°C, a dense nickel layer will grow on the surface of the PI film, and a nickel-treated PI film will be obtained;

[0081] (5) The nickel-treated PI film is immersed in a 90°C gold-immersion solution. At this time, a uniform and dense gold layer will grow on the surface of the PI film to obtain a PI gold-immersion electrode.

[0082] Depend on Figure 5It can be seen that the sensitivity of the curve is 0.72 in the range of 0-2N, 0.48 in the range of 2-4N, and 0.37 in the range of 4-10N. The linearity is 4.62% in the range of 0-2N, 2.93% in the range of 2-4N, and 1.71% in the range of 4-10N.

[0083] Depend on Figure 6 It can be seen from the response time curve that the response time and recovery time of the sensor are both 380ms.

[0084] In summary, the flexible pressure sensor made of cellulose solid electrolyte membrane has a fast response, accurate and stable sensing, and is an excellent flexible pressure sensor.

Claims

1. A flexible pressure sensor based on cellulose solid electrolyte membrane, characterized in that: A cellulose solid electrolyte membrane and PI immersion gold electrode using a phosphoric acid and urea phosphate dissolution system; The preparation steps of the cellulose solid electrolyte membrane are: S1. adding urea phosphate and cellulose to phosphoric acid, and completely mixing and dissolving them by ultrasonication to obtain a mixed solution 1; S2. PVA is added to deionized water, heated to melt at 90 to 95°C, and the PVA and water are mixed uniformly by stirring to obtain a PVA solution; S3. The mixed solution 1 obtained in step S1 is added dropwise to the PVA solution obtained in step S2, and stirring is maintained during the addition; Obtaining an electrolyte solution in which cellulose is dissolved, namely, a mixed solution 2; the mass ratio of the mixed solution 1 added dropwise to the PVA solution is 1:10 to 1.3:10; S4. Pour the mixed solution 2 obtained in step S3 into a mold and dry it in a constant temperature drying oven at 30 to 35°C for 24 to 48 hours to obtain a cellulose solid electrolyte membrane; The steps for preparing the PI immersion gold electrode are as follows: (1) Cleaning the PI film by ultrasonic wave, placing the cleaned PI film in KOH solution for modification, and obtaining a modified PI film; (2) immersing the modified PI film in a nickel sulfate solution at 45 to 50° C., so that nickel ions are adsorbed on the surface of the PI film, thereby obtaining a PI film adsorbed with nickel ions; (3) placing the PI film adsorbed with nickel ions in a sodium borohydride solution to reduce a nickel seed layer on the surface of the PI film to obtain a reduced PI film; (4) placing the reduced PI film into a nickel precipitation solution at 85-90° C., a dense nickel layer will grow on the surface of the PI film, and a nickel-treated PI film will be obtained; (5) The nickel-treated PI film is immersed in a gold-immersion solution at 85 to 90°C. At this time, a uniform and dense gold layer will grow on the surface of the PI film to obtain a PI gold-immersion electrode.

2. A flexible pressure sensor based on cellulose solid electrolyte membrane according to claim 1, characterized in that: The cellulose solid electrolyte membrane has micro-columnar protrusions on its surface after being dried in a mold.

3. A flexible pressure sensor based on cellulose solid electrolyte membrane according to claim 1, characterized in that: In the step S1, the concentration of phosphoric acid is 85 wt %, and the mass ratio of urea phosphate, cellulose and phosphoric acid solution is 1:2 to 6:1.

74.

4. A flexible pressure sensor based on cellulose solid electrolyte membrane according to claim 1, characterized in that: The mass ratio of the amount of the mixed solution 1 added dropwise to the PVA solution in step S3 is 1:

10.

5. A flexible pressure sensor based on cellulose solid electrolyte membrane according to claim 1, characterized in that: The concentration of the KOH solution in step (1) is 4M, the concentration of the nickel sulfate solution in step (2) is 0.05M, the concentration of the sodium borohydride solution in step (3) is 0.025M, and the nickel precipitation solution and gold precipitation solution are from Shenzhen Kosilin Surface Treatment Materials Co., Ltd., the nickel precipitation solution model is KS-N110, and the gold precipitation solution model is HAU-99.

Citation Information

Patent Citations

  • Flexible silver electrode and preparation method thereof

    CN111349934A

  • Preparation method of piezoelectric flexible self-powered sensor battery

    CN115347251A

  • Stretchable yarn type battery and preparation method thereof

    CN116417659A

  • Solid electrolyte and electrochemical system using this solid electrolyte

    JP2005353422A

  • Energy generation and / or storage device based on fibres and thin films

    WO2011039576A1

Cited By

  • A cellulose-based flexible capacitive pressure sensor with electric driving potential and a preparation method thereof

    CN122793323A